THE INSTITUTIONAL POLICY MODEL OF WALI NANGGROE FOR COMMUNITY RESILIENCEPOST- CONFLICT IN ACEH - DAHLAN A. RAHMAN; ENDANG LARASATI; SRI SUWITRI; BUDI PUSPO PRIYADI (Journal of Business & Tourism, 2021)
The Wali Nanggroe Institution, which functions as an adhesive media for the Acehnese people politically, is still considered unable to implement the Helsinky MoU. Although there have been several studies of political dynamics in Aceh after Helsinky, there have not been any studies that have explored the implementation of policies regarding the Wali Nanggroe Institution in Aceh. Although a memorandum of understanding was signed between the Government of the Republic of Indonesia and the Mardeka Aceh Movement (Independence of Aceh), the implementation of the MoU was not yet complete. The lack of attention of researchers about the implementation of the Wali Nanggroe policy because there are many parties who are unsure about the existence of the institution. This study is an academic response in order to find scientific answers to the presence of the Wali Nanggroe Institution which is formulated in the form of three research questions, namely How is the implementation of Qanun Number 9 of 2013 concerning the Wali Nanggroe Institution, what are obstacles and supportive factors of policy implementation - policy of the Wali Nanggroe Institution Qanun and What is the Wali Nanggroe Institution's Policy Implementation Model. The author combines qualitative data of 30 informants to find the cases as well as conflict resolution models in Aceh. The quantitative data support answers that are in accordance with the demands of research questions. The results of the study show that the Wali Nanggroe Institute was born after the Helsinki MoU to resolve the Aceh conflict that was legally recognized by the State to maintain the integrity of peace, it has the right to immunity. Qanun is influenced by aspects of policy content. It unites the Aceh political leaders who are conflicting in preparing budgets in the Aceh Parliament.Qanun alsohas the power to regulate upper house and functional assemblies. The implementation of qanun has been running since the issuance of Law Number 11 of 2006 concerning the Government of Aceh (UUPA). Legal basis for the birth of the Nanggroe UUPA institution Article 96 (1) The Wali Nanggroe Institution is an indigenous leadership as an independent unifying community, not a political and government institution in the Province of Nanggroe Aceh Darussalam. Therefore, the author concludes that the policy implementation of the WaliNanggroe Institution in Aceh is a new approach. The Government of Aceh, the Government of Indonesia and countries experiencing almost the same conflict model can use the results of this study to encourage conflict resolution through a permanent political settlement.